Peningkatan Hasil Pembelajaran dan Motivasi Dalam Pembelajaran Gerak Dasar Atletik (Lompat Jauh) dengan Metode Bermain Kelas V Sekolah Dasar - Khairul Zikri; Herli Pardilla (Joska: Jurnal Isori Kampar, 2024)
This study aims to enhance educational results in long jump athletics through engaging teaching methods for fifth-grade students. The enjoyable methodology is selected as an effective instructional approach to elevate students' motor skills. The research employs a class action design with two iterative cycles involving planning, execution, observation, and reflection. The sample comprised 30 fifth-grade students. Data collection was conducted systematically through observations, proficiency assessments, and questionnaires. Results indicated significant improvement in long jump performance, with average scores rising from 67.3 in the pre-cycle to 72.2 in cycle I and 78.8 in cycle II. Additionally, student motivation and engagement increased significantly, from 60% participation in the pre-cycle to 90% in cycle II. In conclusion, the playful pedagogical method was effective in enhancing basic motion learning outcomes in long jump athletics for fifth graders.